148 Identification of Weaknesses in Resident Socioeconomic Training: Results of a National Survey by the Council of State Neurosurgical Societies. (August 2015) - Mukherjee, Debraj; Park, Michael S.; Bekelis, Kimon; Braca, John A.; Colen, Chaim B.
Abstract : INTRODUCTION: Over the past decade, new national guidelines and requirements ranging from ACGME mandated duty hour restrictions to the development of The Neurological Surgery Milestone Project have rapidly altered the shape of current neurosurgical education and training. This national survey of neurosurgical residents within all levels of training was performed with support from the Council of State Neurosurgical Societies and the Young Neurosurgeons Committee in an effort to quantify the relative readiness of residents to venture into practice and to understand the socioeconomic issues impacting our field. METHODS: A 12-question online survey (SurveyMonkey) was sent to all active neurosurgical residents throughout the country. This survey was made available to residents in Spring 2014 and Winter 2015. RESULTS: A total of 235 neurosurgical residents responded to the survey. The vast majority of residents (91.1%) reported having no formal socioeconomic curriculum with most (76.6%) receiving socioeconomic training only via informal discussions. The vast majority (77.2%) felt there were weaknesses in their training, but most (68.9%) felt at least adequately prepared to enter practice. The majority of residents (78.8%) intend to pursue subspecialty training, and it appears this trend toward specialization is driven by personal interest (80.9%) rather than by perceived weaknesses in training (5.0%). Specific areas of perceived weakness in socioeconomic training, where the majority of residents felt inadequately prepared, included: minimizing malpractice risk and liability (52.8%), entrepreneurship (59.0%), practicing cost-effective medicine (63.4%), medical coding/billing (76.6%), understanding pay-for-performance (78.3%), business and economics of neurosurgery/health care (81.3%), evaluating a practice opportunity (83.4%), practice management (86.4%), and negotiating a contract (87.7%). CONCLUSION: In a national survey of neurosurgical residents, the vast majority of respondents felt their training lacked adequate socioeconomic training. Specific areas of weakness have been identified, and new initiatives are needed within the field of neurosurgical education to fill this void.